CLINICAL PATTERNS OF MALABSORPTION SYNDROMES IN CHILDREN - Ginel Baciu; Carmen Baciu; Cristina Maria Mihai; Tatiana Chisnoiu; Ramona Mihaela Stoicescu; Adriana Luminita Balasa; Adriana Mocanu; Lorenza Forna; Alexandru Paul Baciu (Romanian Journal of Oral Rehabilitation)
Malabsorption syndrome encompasses a variety of gastrointestinal disorders that impair nutrient absorption in children, presenting wide range of clinical manifestations. This study focused on characteristics of the clinical manifestations and underlying etiologies of malabsorption syndrome in pediatrics population. Material and methods: A prospective cohort study was conducted involving 29 children presenting with symptoms suggestive of malabsorption syndrome. Clinical data, including symptoms, growth parameters, and nutritional status, laboratory both at the time of admitting and during treatment were collected. Diagnostic investigations included serological tests, stool analysis, imaging studies, and histopathological examination. Results: The most frequent clinical manifestations were abdominal symptoms (85%), respiratory infections (65 %), anemia (45 %) and vitamin deficiencies (58%). Celiac disease (51%), cystic fibrosis (32%), and Cow’s milk protein allergy (17%) were the leading causes. Conclusions: Serological tests are important for celiac disease diagnosis, while stool analysis is used to identifying lactose intolerance and infections. Diarrhea and weight loss are prevalent clinical manifestations of pediatric malabsorption syndrome.